Rural Finance Policies 7 - Rural financial services for poverty alleviation: the role of public policy - Sharma, Manohar; Zeller, Manfred (International Food Policy Research Institute, 2000)
For poor rural families in developing countries, access to credit and savings facilities has the potential to make the difference between grinding poverty and an economically secure life. Well-managed savings facilities permit households to build up funds for future investment or consumption. Credit enables them to tap finances beyond their own resources and to take advantage of profitable investment opportunities. Credit and savings also serve as insurance for the poor. In rural areas of developing countries, short-term loans or past savings are often used to provide basic necessities when household incomes decline temporarily — after a bad harvest or between agricultural seasons, for example....Successful financial outreach to the rural poor requires institutional innovations that reduce the risks and costs of lending small amounts of money. So far, most innova-tions in microfinance have come from nongovernmental organizations (NGOs) that do not have commercial profit as their principal objective. By taking fresh approaches, these new microfinance institutions have penetrated rural financial markets and serviced an underclass of borrowers in a way that was unimaginable some 20 years ago....One important lesson that is becoming increasingly clear: there is no single institutional blueprint for success.